2020
DOI: 10.5604/01.3001.0014.1678
|View full text |Cite
|
Sign up to set email alerts
|

Work Engagement, Organizational Commitment and the Work Satisfaction of Tax Administration Employees: The Intermediary Role of Organizational Climate and Silence in the Organizations

Abstract: The aim of the presented study was to verify the relationship between the level of work engagement and organizational commitment and work satisfaction experienced by employees, taking into account intermediary variables—i.e. the climate at the organization and the phenomenon of silence in the organization. The survey involved a total of 131 employees of the National Revenue Administration, including 35 males and 96 females. Five methods were used to verify the questions and research hypotheses: Allen and Meyer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The positive association between self-leadership and work performance found from the results of our study further supports the notion of Marques-Quinteiro et al ( 2019 ) and Alnakhli et al ( 2020 ) that self-leadership strategies lead employees to adapt to the situation that would improve their performance. Our findings also support the works of Peplińska et al ( 2020 ) who reported a positive relationship between work engagement and organizational commitment and Tisu et al, (2020) who found a link between work engagement and job performance. These results link back to the initial concept of self-leadership which is of the view that intrinsic motivation and self-influence are driven by high level of organizational standards (Neck & Houghton, 2006 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The positive association between self-leadership and work performance found from the results of our study further supports the notion of Marques-Quinteiro et al ( 2019 ) and Alnakhli et al ( 2020 ) that self-leadership strategies lead employees to adapt to the situation that would improve their performance. Our findings also support the works of Peplińska et al ( 2020 ) who reported a positive relationship between work engagement and organizational commitment and Tisu et al, (2020) who found a link between work engagement and job performance. These results link back to the initial concept of self-leadership which is of the view that intrinsic motivation and self-influence are driven by high level of organizational standards (Neck & Houghton, 2006 ).…”
Section: Discussionsupporting
confidence: 92%
“…As normative commitment refer to the sense of willingly benefiting and meeting the organizational expectations, Schaufeli et al (2002) indicated that individuals who are highly engaged in their work tend to have an inner belief that they can meet the expectations and demands of their jobs. This engagement and high inclusion in their work will also increase their normative commitment (Peplińska et al, 2020). In view of intrinsic motivation theory, the work itself can create an internal sense of motivation which leads to actions that are for the organizational benefit (Miller et al, 1988).…”
Section: Work Engagement and Normative Commitmentmentioning
confidence: 99%
“…The findings confirmed the hypothesis which means that the higher teachers are committed to their school the higher they will be engaged to their work. The studies conducted on teachers ( Çağrı San and Tok, 2017 ; Pieters and Auanga, 2018 ) and other samples such as banking employees ( Adi and Fithriana, 2020 ), private and public sector employees ( Agyemang and Ofei, 2013 ), undergraduate students ( Babcock-Roberson and Strickland, 2010 ), airline companies ( Li et al, 2010 ), National Revenue Administration employees ( Peplińska et al, 2020 ), also put forward consistent findings with this study, while food processing plant employees ( Gota, 2017 ) has found that WE is negatively associated with affective commitment. Based on these findings, it can be said that this study contributed to the literature by proving that WE is up to OC.…”
Section: Resultsmentioning
confidence: 99%
“… Zhang et al, 2018 ). It has a negative effect on the phenomenon of organizational silence and a positive impact on commitment ( Peplińska et al, 2020 ). The strengthening of these variables by the organization is particularly important during the COVID-19 pandemic, when many companies are struggling with problems resulting from the restrictions and are afraid of further consequences for their functioning.…”
Section: Discussionmentioning
confidence: 99%